1Department Of Complexity Science and Engineering,Devision Of Trans Disciplinary Science,University Of Tokyo, JAPAN. - Adharvanachary, M (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Abstract: Some Hitherto unknown complexes of Alloxan Thiosemicarbazone and Substituted Thiosemicarbazones with Au(III) have been synthesized and characterized by elemental Analysis,spectral viz. FT-IR,NMR,UV-Vis,Mass etc, magnetic, thermal and conductance studies.All complexes are crystalline powders decomposed by mineral acids.the spectral and other data indicate that all the Au(III) complexes are tetrahedral.The ligand,its Schiff?óÔé¼Ôäós Bases and and metal chelates would be screened in-vitro for anticancer activity against some cancer Cell lines.